ADVANCED HODGKIN LYMPHOMA: A NEW ERA OF THERAPY - Eldad J Dann (Mediterranean Journal of Hematology and Infectious Diseases)
Therapy of advanced Hodgkin lymphoma (HL) is a rapidly changing field due to a lot of currently emerging data. Treatment approaches are presently based on either the Kairos principle of giving aggressive therapy upfront and considering de-escalation of therapy if the interim PET/CT is negative or the Chronos principle of starting with ABVD followed by escalation of therapy for patients with positive interim PET/CT. The International Prognostic Score (IPS) is still valid for decision-making regarding the type of initial therapy, since patients with a high score do have an inferior progression free survival (PFS) with ABVD compared to those with a low score. Escalated BEACOPP administered upfront improves PFS; however, increase in the overall survival (OS) has not been confirmed yet, and this therapy is accompanied by elevated toxicity and fertility impairment. Completion of ongoing and currently initiated trials could elucidate multiple issues related to the management of HL patients.